Could scalp pain be a type of unclassified headache? - Silva-Néto, Raimundo Pereira; Almeida, Denise Evelyn Machado de (Headache Medicine, 2024)
The scalp is the structure that covers the skull. It is commonly affected by painful processes resulting from infestations, infectious or inflammatory diseases. This pain located in the scalp does not have well-defined clinical characteristics and is not yet included in the ICHD-3 diagnostic criteria. The authors suggest including this pain in the next classification of headaches as a headache attributed to a scalp disorder.